A cross-sectional study of salmonella in pork products in Chiang Mai, Thailand - Sanguankiat A. (2014)
The occurrence of Salmonella in food of animal origin in Chiang Mai province was investigated by using a cross-sectional study during several phases of the pork production chain (cutting, transport, and retail) and of the environment in the cutting unit of a slaughterhouse. In total, 173 pork samples were obtained during the cutting phase, 173 samples from transported pork, 200 samples from retail products, and 300 samples from the slaughterhouse environment. Salmonella was detected in 55.5% of freshly cut pork, 70.5% of transported pork, and 34.5% of retail products. The five most prevalent Salmonella serotypes identified were Rissen (45.3%), Typhimurium (16.3%), Krefeld (10.6%), Stanley (6.3%), and Lagos (6.0%). Carcass contamination prior to cutting and in the slaughterhouse environment appeared to be important sources of Salmonella in transported pork and retail products. As Salmonella was also found during early stages of the slaughter process, attention should focus on all stages of the pork production chain to reduce contamination level and consumer risk of infection. © 2010, Mary Ann Liebert, Inc.